Potensi Jenis Dipterocarpaceae di Hutan Produksi Cagar Biosfer Pulau Siberut, Sumatera Barat - Endro Subandriono; M. Bismark; N. M. Heriyanto (Buletin Plasma Nutfah, 2010)
The study ofDipterocarpaceae was done in November 2007 in SiberutBiosphere Reserve. This study conducted on threes sample plotof 0.75 ha in primery forest, logged over area (LOA) <1 yearand LOA 5 years. The result showed there were three speciesof Dipterocarpaceae: Dipterocarpus elongatus Korth., Shoreajohorensis Foxw. and Hopea mangarawan Miq. The density oftree and pole in primary forest were about 24 individual/ha and13.34 individual/ha, there were 9.3 individual/ha and 4individual/ha in LOA <1 year, than this density were 8individual/ha and 5.34 individual/ha in LOA 5 years. Forsapling and seedling, these densities were about 29individual/ha and 5.417 individual/ha in primary forest, 5individual/ha and 3.750 individual/ha in LOA <1 year, 89individual/ha and 883 individual/ha in LOA 5 years.Community couple between primary forest and LOA wich hassimilarity index value more than 50%; at tree stage, it was68,83% comparing primary forest and LOA <1 year; at polestage it was 62.62% comparing primary forest and LOA 5years; at sapling stage, there were 53.29% and 66,27%comparing with LOA <1 year and LOA 5 years; at seedlingstage it was 88.66% compared to primary forest and LOA <1year. Similarity index between LOA <1 year with LOA 5years, there were 60.26% for tree stage, 90.05% for pole stageand 51.13% for seedling stage.